LITHOLOGIC FEATURES OF LOW PERMEABLE OIL AND GAS SATURATED RESERVOIR ROCKS IN THE NEOGENE SEDIMENTS THICKNESS IN BUTSIVSKE GAS FIELD AS AN ANALOG - OSTASH, Oleh; OMELCHENKO, Valeriy; KALYNII, Tetyana (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. The article investigates the problem of low-porosity and low-permeability reservoir rocks, which are relevant for hydrocarbon deposits in the Neogene sediments of the Outer Zone of the Precarpathian Trough. The low efficiency of traditional methods for assessing the gas saturation and productivity of these rocks creates significant obstacles to their development, which requires the use of new approaches. Methods. The study was conducted on the basis of the analysis of core material taken from the productive horizons of the Butsivske gas field. A detailed petrophysical analysis was performed, including the assessment of the textural and structural features of the rocks, their mineral composition, as well as the characteristics of porosity and permeability. The methods of saturation of samples with dyes, microscopy and granulo-metric analysis were used. Results. It was established that low-porosity reservoir rocks have a significant influence on texture, structure and mineral composition of their filtration and capacity properties. The main type of porosity is subcapillary, which provides limited permeability. Analysis of the samples showed that the proportion of effective pore space involved in filtration is low (less than 40% in the total open space structure). The main productive horizons are sandy-clayey deposits of the Lower Dashava formation. Conclusions. The study confirmed that it is necessary to apply chemical treatment methods, such as acid treatments, which contribute to the creation of connected channels in the pore space to intensify gas production from low-porosity rocks. The results obtained have practical significance for optimizing the development of gas horizons in the Precarpathian trough and can be used in planning exploration and exploitation works.